Hazard Analysis Critical Control Point (HACCP) in Sweet Potato’s Liquid Sugar - Mahmudatusaadah, Ai; Sudewi, Sudewi (INVOTEC, 2016)
To ensure the safety of food products to the consumer, required the application of Hazard Analysis Critical Control Point (HACCP). Liquid sugar is a food product which can be eaten directly or used as additives in the processing of other products. Stages in the HACCP plan includes identification of hazard analysis critical control point (CCP), the determination of the limit of danger, CCP monitoring, corrective action against danger verification, and documentation. Results of hazard identification no physical harm in the form of pebbles, hair; pesticide chemical hazards, biological hazards ants and black shank. CCP 1 was washing materials, CCP 2 was incubation, CCP 3 was Packaging. Critical limits for all hazards should be zero. Corrective measures must be of good quality raw materials. Wash in running water. Incubation at 400 C. Packaging using sterile packaging.